Clinical efficacy of high dose treatment with teicoplanin (TEIC) against MRSA infections and trough concentration of TEIC - Kamisasa, Hiroshi; Mochizuki, Toru; Unemoto, Kyoko; Kurokawa, Akira; Makin, Masahiko; Noguchi, Shusaku; Ueda, Yasuharu (Japanese Journal of Chemotherapy, 2007)
We analyzed the clinical efficacy of high dose teicoplanin (TEIC)(1, 600 mg/24 h for the first day and 800 mg/24 h thereafter) and plasma trough concentration of TEIC in MRSA infections in Emergency and Critical Care Medicine, to examine the relationship between a change in the trough concentration after administration of this drug and efficacy and safety. Results are as follows: 1. The clinical efficacy of TEIC against 10 cases of pneumonia, 2 of septicemia with wound infection due toMRSA was 100%. 2. The bacteriological effectiveness of TEIC consisted of 9 eradicated, 1 decreased, 2 replaced, and O unchanged. Among 8 patients treated with TEIC alone, it consisted of 7 eradicated, O decreased, 1 replaced, and O unchanged. Among 4 patients concomitantly treated with other drugs, it consisted of 2 eradicated, 1 decreased, 1 replaced, and O unchanged. Four of 12 patients showed multibacterial infection with Pseudomonas aeruginosa. 3. No case administered TEIC was found to have any side effects or abnormal laboratory findings. 4. The trough blood TEIC level slightly decreased to 17.5 ±6.7 μg/mL on day 2 and 16.3 ±6.3μg/mL on day 4, showing a steady state, and accumulation of TEIC was as mild as 20.5 ±6.9μg/mL on day 8. There 5. High-dose treatment with TEIC showed highly sharp efficacy and high safety, which was considered to be a very useful method for treatment of severe MRSA infections. was no variation of blood concentrations in the respective patients, moreover.